The Impact of Artificial Intelligence on Digital Health and Vascular Surgery - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2025)
Discover how artificial intelligence is transforming digital health and vascular surgery with advanced diagnostics, predictive analytics, and personalized care.
Keywords: Artificial Intelligence; Digital Health; Vascular Surgery; Medical Imaging; Healthcare Innovation